Scientometric Study on Tourism Development - Álvarez – Montoya, Gladys Rosario (Universidad Francisco de Paula Santander, 2024)
Tourism is a topic of worldwide interest, since it is an area in constant development and evolution, as well as being of vital importance because it is a source of economic, social, cultural, structural and environmental development in tourist areas or destinations. The purpose of the study is to analyze the scientific production on tourism de-velopment based on the scientometric analysis that allows characterizing the state of the art by finding the key words in trend, most cited authors, and thematic areas of tourism development in order to channel future studies. The methodology is based on the scientometric analysis in the scopus database. The results of the study indicated a high scientific productivity due to the fact that an average of 1132 articles are generated per year, with the year 2021 being the year with the most publications on the subject (2068 publications) and among the main scientific journals that are talking about tourism development, the one that stands out the most is the journal Sustainability Switzerland (1533 publications).